Evaluation of inhibitory efficacy of ginger extract on Staphylococcus aureus bacteria - Mohammed, Shaimaa Zaidoun Nafi; Al-Dabbagh, Wael Yassin (Journal of medical and pharmaceutical sciences, 2017)
This study aimed was to evaluate the effect of microbial antibody on water ginger extract and to determine its inhibitory effect on Staphylococcus aureus bacteria which cause urinary tract infection concentrations of the extract 100% , 75% , 50% ,25 % mg / ml) were used and the minimum inhibitory concentration of the extract was measured . The results showed that Minimum inhibition concentration   (MIC) of the ginger extract was 25% .the water extract effective against the bacteria . the results were compared with the effect of certain antibiotics such as Nitrofurantionl (F), Gentamycin (CN) , Ciprofloxacin (CIP), Trimethoprim (TMP) . The effect of ginger extract has had a better antibacterial effect than some antibiotics.
Keywords: Staph; aureus; Staph. aureus; MIC; ginger; inhibitory activity